2012
DOI: 10.1088/0004-637x/746/2/154
|View full text |Cite
|
Sign up to set email alerts
|

A Revised Age for Upper Scorpius and the Star Formation History Among the F-Type Members of the Scorpius-Centaurus Ob Association

Abstract: We present an analysis of the ages and star-formation history of the F-type stars in the Upper Scorpius (US), Upper Centaurus-Lupus (UCL) and Lower Centaurus-Crux (LCC) subgroups of Scorpius-Centaurus (Sco-Cen), the nearest OB association. Our parent sample is the kinematically-selected Hipparcos sample of de Zeeuw et al. (1999), restricted to the 138 F-type members. We have obtained classification-resolution optical spectra and have also determined the spectroscopic accretion disk fraction. With Hipparcos and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
568
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 551 publications
(641 citation statements)
references
References 106 publications
67
568
5
1
Order By: Relevance
“…As we discussed in Sect. 4, there is some disagreement between our own results and those of Pecaut, Mamajek, & Bubar (2012). However, we note that the use of Pecaut, Table 2. combination of empirical isochrones and the models of Dotter et al (2008) and found an age for USco of 11±1 Myr.…”
Section: Evolutionary Status Of the Investigated Starscontrasting
confidence: 59%
See 3 more Smart Citations
“…As we discussed in Sect. 4, there is some disagreement between our own results and those of Pecaut, Mamajek, & Bubar (2012). However, we note that the use of Pecaut, Table 2. combination of empirical isochrones and the models of Dotter et al (2008) and found an age for USco of 11±1 Myr.…”
Section: Evolutionary Status Of the Investigated Starscontrasting
confidence: 59%
“…The only relevant exceptions are EPIC 204399980 (HIP 79476) and 204494885 (HIP 80130). For the first star we find an effective temperature about 500 K larger than that reported by Pecaut, Mamajek, & Bubar (2012), who in turn refer to Vieira et al (2003). However, on the basis of high-resolution spectroscopy, Carmona et al (2010) discussed the spectral type of this star, concluding that it cannot be later than A5Ve and estimated a T spec eff =8200 K, almost identical to our value.…”
Section: Caos Spectrasupporting
confidence: 39%
See 2 more Smart Citations
“…We conclude that our detection of Kepler-78 is not strongly sensitive to spot model assumptions or to individual RV measurements. 44 . Additional iron and calcium lines are labeled.…”
Section: Methodsmentioning
confidence: 99%